Ideal L2 self, acculturation, and Chinese language learning among South Asian students in Hong Kong: A structural equation modelling analysis. (April 2016) - Gu, Mingyue (Michelle); Cheung, Derek Sin-pui
Abstract: This study takes the initiative to use structural equation modelling to evaluate a motivational model which subsumes some hypothesized links between L2 ideal self, acculturation to the mainstream society, acculturation to the heritage culture, and learners' intended effort to learning the mainstream language as an L2 among immigrant students in a host context. Data was collected from 390 secondary students with ethnic minority backgrounds in Hong Kong. It is found that L2 ideal self has a direct effect on intended effort and an indirect effect through the acculturation to mainstream culture. It is also found that parental encouragement contributes to intended efforts both directly and indirectly via impacting L2 ideal self. The findings imply that promoting ethnic minority students' Chinese language ideal self would help construct their bicultural identity.